Molecular genetic evaluation of myeloproliferative neoplasms. (14th May 2015) - Azzato, E. M.; Bagg, A.
Summary: The classical myeloproliferative neoplasms (MPNs) consist of chronic myelogenous leukemia (CML) and the non‐CML MPNs, polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF). Molecular testing plays a crucial role in each of these disease entities. In this review, we discuss the role and caveats of BCR‐ABL1 fusion transcript evaluation in CML diagnosis and monitoring, as well as ABL1 kinase mutation testing in the setting of tyrosine kinase inhibitor resistance. We also focus on JAK2, MPL, and CALR mutations in PV, ET, and PMF.